2017
DOI: 10.31768/2312-8852.2017.39(1):78-85
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSTIC CHALLENGES WITH INTRAORAL MYELOID SARCOMA: REPORT OF TWO CASES & REVIEW OF WORLD LITERATURE

Abstract: Background: Myeloid sarcomas (MS) are rare extramedullary tumors composed of blasts of myeloid lineage that either precede, follow or present concomitantly with acute myeloid leukaemia (AML) or myeloproliferative neoplasms. The diagnosis of MS is especially challenging in patients without an antecedent history of leukemia. Methods: We present 2 cases of intraoral MS that presented as de novo lesions. A detailed review of cases of intraoral MS that either preceded or presented along with leukemia has been done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In the present case, the patient was an 81‐year‐old man, presenting a nodular, sessile lesion, measuring about 2 cm at its largest point, and was purple and hemorrhagic. In accordance with the literature, the patient was asymptomatic, but the mandible represented the majority of the oral manifestations, which is not consistent with this case; however, GS has been reported at almost all intraoral sites (Table ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present case, the patient was an 81‐year‐old man, presenting a nodular, sessile lesion, measuring about 2 cm at its largest point, and was purple and hemorrhagic. In accordance with the literature, the patient was asymptomatic, but the mandible represented the majority of the oral manifestations, which is not consistent with this case; however, GS has been reported at almost all intraoral sites (Table ).…”
Section: Discussionsupporting
confidence: 77%
“…Although some studies have recommended that chemotherapy is more effective than radiotherapy or surgical resection, there is no consensus regarding the management. It was reported that GS associated with chronic myeloid leukemia (CML) or myelodysplastic syndrome has a worse clinical outcome when compared to MS with AML . In addition, GS prognosis may be poor, with survival times varying among different studies …”
Section: Discussionmentioning
confidence: 99%
“…Considering the 89 cases of oral MS previously published in the English literature, the average age of the patients is 45 years (ranging from 1 to 89 years), with slight predilection for females (1,2:1). The mandible is the most common affected site (28 cases), followed by maxilla (20 cases), gingiva (13 cases), and palate (seven cases) ( 1 - 15 ). MS affected multiple intraoral anatomical sites in eight cases, six of them with concomitant involvement of maxilla and mandible ( 5 , 7 , 8 , 11 , 13 - 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…APL is characterized by the predominance of abnormal promyelocytes in the bone marrow and identification of a specific chromosomal translocation t(15;17)(q24.1;q21.1) resulting in a fusion transcript between the genes promyelocytic (PML on chromosome 15) and retinoic acid receptor alpha (RARA on chromosome 17). The most common diseases associated with oral MS are AML (43 cases), followed by myelodysplastic syndrome (11 cases), and chronic myeloid leukemia (seven cases), nevertheless 14 patients with oral MS did not present nor developed associated leukemia or myelodysplastic neoplasms ( 1 - 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation